Μελέτη της επίδρασης της μεθόδου σύνθεσης στηριζόμενων καταλυτών Pt για την αντίδραση καταλυτικής αναγωγής των οξειδίων του αζώτου (NOx) με υδρογόνο (Η2) παρουσία οξυγόνου (O2) - Αχιλλέως, Ανδρούλα (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
The objective of this postgraduate thesis is to study the catalytic reduction (activity and selectivity to N2O and NH3) of NO with hydrogen, in the presence of oxygen (NO/H2/O2) on monometallic supported catalysts (0.1%w/w Pt/Al2O3 and 0.1%w/w Pt/MgO-CeO2), using a synthesis based on the wet impregnation method with three different solvents (i) water, (ii) isopropanol, and (ii) a solution of “ink”. The ultimate goal of this research is to find the most suitable catalyst for the aforementioned reaction, that is the catalyst which shows the highest activity to the unwanted toxic gas of NO and the highest selectivity to the harmless nitrogen gas (N2). It is also noteworthy that the reaction of NO/H2/O2 was studied under conditions of high concentration of O2 (20% O2/He vol%, leanDe-NOx). In that way, the oxidising conditions that are commonly found in the exhaust gases of a pollutant (p. x., power station, ship), were simulated. It was considered necessary to proceed in a physicochemical characterization (surface morphology) of the catalysts under study, using various techniques. More specifically, the methods that were used include B.E.T. (measurement of specific surface area and pore size distribution) and TPD-H2 (Temperature Programmed Hydrogen Desorption) in order to study the heterogeneity of the surface (surface number and kind of metal centers) and to find the apparent dispersion of the metals. The 0.1%w/w Pt/MgO-CeO2 catalyst (wet impregnation - “ink method”) appears to have the highest activity (XNO,%) and the lowest selectivity to N2O (SN2O,%) at low temperature, as well as the largest operating temperature window for the reaction NO/H2/O2. The second best catalyst was the 0.1%w/w Pt/Al2O3, which was also prepared using the same method. In conclusion, the results obtained from the synthesis of the 0.1% w/w Pt/MgO-CeO2 catalyst based on the wet impregnation method through the use of “ink” solvent (wet impregnation - “ink method”), regarding the reaction of NO/H2/O2, are considered important for future research in the domain of printing catalysis. Printing catalysis is considered as a quite promising process, which can bring considerable advantages over conventional methods.
Keywords: Catalytic reduction; Catalysts; Καταλυτική αναγωγή; Καταλύτης